The role and potential of forage legumes in alley cropping live mulch and rotation systems in humid and subhumid tropical Africa - Mulongoy, K.; Kang, B.T. (International Livestock Centre for Africa, 1986)
Discusses the role and potential of forage legumes in alley cropping, live mulch and in situ mulch systems in humid and subhumid tropical Africa. Examines forage legume species for alley cropping; nutrient contribution from leguminous trees and shrubs grown in hedgerows, forage legume in situ and live mulches, soil restorative and protective value of in situ and live mulches, nitrogen fixation and nitrogen contribution, effects on nematodes, weeds, and crop yield.